Investigating risk disclosure practices in the annual reports of UK non-financial companies - Papadopoulos, Loucas (2013)
It is generally acceptable that there is a need for a more transparent risk reporting. In light of the recent credit crunch, this study examines the risk disclosures in the annual reports of UK non-financial companies in 2007 and 2010. Using a self-constructed risk disclosure index, the study explores the association between risk disclosures and company size and risk level. The study also compares the amount of risk disclosures in the annual reports of 2007 and 2010 and across three different industries. The findings suggest that there is an association between risk disclosures and company risk level and that companies from different industries have disclose different amounts of risk information. The study also finds an increase in the amounts of risk disclosures after the financial crisis.